Visualisasi Spasial Akulturasi Bahasa Bugis Terhadap Masyarakat Suku Tolaki Di Kecamatan Samaturu Kabupaten Kolaka - Risnawati; Kamur, Sudarwin; Hariyadi, Eko; Nasarudin; Samsi Awal (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
The familiarity of social life between the Bugis and Tolaki communities in Samaturu District, Kolaka Regency covers various sectors of life, so that it affects the way of communication of the indigenous people, especially the Tolaki people, it causes a process of cultural acculturation in the form of the language used in the Tolaki people, therefore this needs to be visualized spatially and identify the factors that cause it. This study aims to provide a spatial visualization of Bugis language acculturation to the Tolaki community and the factors that cause the Tolaki community to be able to use Bugis language in communicating with Bugis community groups in Samaturu Sub-district, Kolaka Regency. The respondents of the study amounted to 339 Tolaki people spread across 14 villages in Samaturu District, Kolaka Regency. Data was collected using questionnaires and analyzed in a quantitative descriptive manner. The results of the study concluded that there are 10 villages where the Tolaki people are fluent in Bugis language and there are 4 villages where the Tolaki people are not fluent but still know the meaning of the Bugis language. In addition, there are three main factors that cause the Tolaki community group to be fluent in using the Bugis language, the three factors are social interaction/social contact, living environment, and marriage. Even so. The fluency of the Tolaki Tribe community in Samaturu District, Kolaka Regency in using the Bugis language does ot necessarily eliminate its own regional languange, this shows that the acculturation process does not touch all cultural elements but only element regional languages that are learnend and used in communication